Immediacy and Distance: Koch, Oesterreicher, and Digital Communication between Orality, Literacy, and Mediality - Laser, Bjoern (Nexus Publishing NXP, 2025)
The digital era has brought with it a wealth of ever new modes of communication, media formats, and communication spaces. In German speaking countries the distinction of “language of immediacy” and “language of distance” is frequently used to explain certain linguistic and semiotic features of digital communication. This follows a concept first published in 1985 by German Romance philologists Peter Koch and Wulf Oesterreicher, the core idea being that the question of written or spoken language is not only a matter of code but also of conception, and that the manifest features of communicative acts depend on the conditions of communication. This paper aims to introduce the concept and to explain why it seems to be ubiquitous in German speaking contexts, but is little known internationally. It connects the Koch-Oesterreicher-model to the similar works of Douglas R. Biber, discusses its limitations regarding affordances in digital environments, and finally shortly asks for its relevance in language didactics and especially foreign language teaching.